Report of Caliothrips phaseoli (Hood) (Thysanoptera: Thripidae: Panchaeothripinae) in onion in Panama - Barba-Alvarado, Anovel Amet (2023)
Introduction. Thrips (Thysanoptera) encompass a variety of phytophagous species that have an impact on the development of agriculturally important plants. Objective. To identify the species and damage caused by thrips associated with onion (Allium cepa L.) cultivation in the Arco Seco region of Panama. Materials and methods. The study was carried out from December 2020 to April 2021 in two onion-producing locations in the Arco Seco region of Panama. Fifty onion plant samples were taken per location. The species of thrips present, the number of thrips specimens captured in each life stage, the percentage of plants with damage and the characteristics of the damage were identified. Results. The species Caliothrips phaseoli (Hood) (Thysanoptera: Thripidae: Panchaeothripinae) caused lacerations, spots, and leaf drying in 80 % of the onion plant samples from El Ejido locality. Among the captured specimens, 47.69 % were female, 46.30 % were immature, and 6.02 % were male. Conclusions. Damage to onions caused by C. phaseoli was recorded for the first time in the Republic of Panama. The knowledge generated represents the initial step for phytosanitary surveillance of this pest in onion cultivation.